Transumbilical Surgery for Duodenal Stenosis in a Child with Situs Inversus: The First Report - Isamu Saeki; Yu Ueno; Wataru Mukai; Reisuke Imaji; Takashi Akiyama (Hindawi Limited, 2017)
Background. Situs inversus is a rare congenital anomaly with a reported incidence of only 1 in 5,000 to 10,000 live births. Congenital duodenal stenosis complicated with situs inversus is an even rarer entity. Case Presentation. A 1-year-old girl with situs inversus who had undergone a hemi-Fontan procedure against a single ventricle in our hospital was referred to our department for vomiting and failure to thrive. An upper gastrointestinal contrast study and endoscopy revealed duodenal stenosis. A transumbilical radical operation as a minimally invasive surgery was successfully performed. After the surgery, she stopped vomiting, and the postoperative course was uneventful with good cosmetic results. Conclusions. To our knowledge, this is the first report of transumbilical surgery for congenital duodenal stenosis with situs inversus as minimally invasive surgery. Transumbilical surgery to situs inversus patient can be performed safely and lead to good cosmetic outcome.